2011
DOI: 10.1017/s1751731111000280
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile in white alpaca (Vicugna pacos) skin

Abstract: A cDNA library from white alpaca (Vicugna pacos) skin was constructed using SMART technology to investigate the global gene expression profile in alpaca skin and identify genes associated with physiology of alpaca skin and pigmentation. A total of 5359 high-quality EST (expressed sequence tag) sequences were generated by sequencing random cDNA clones from the library. Clustering analysis of sequences revealed a total of 3504 unique sequences including 739 contigs (assembled from 2594 ESTs) and 2765 singletons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This also implies that phenotypic characteristics determined by these genes may show particular inheritance patterns due to close linkage. Among the many known molecular components of the mammalian hair follicle (Rompolas and Greco, 2013), keratins and collagens are perhaps most studied (Toivola et al, 2015) and associated with various hair texture characteristics in several mammalian species including humans (Shimomura et al, 2010), dogs (Cadieu et al, 2009), horses (Balmer et al, 2017; Morgenthaler et al, 2017) and alpacas (Fan et al, 2011). Here we considered as candidate genes for alpaca hair texture also genes related to apoptosis regulation and formation of the hair follicle, such as CTNNB1 , TNFSF12 , and DAB2IP .…”
Section: Discussionmentioning
confidence: 99%
“…This also implies that phenotypic characteristics determined by these genes may show particular inheritance patterns due to close linkage. Among the many known molecular components of the mammalian hair follicle (Rompolas and Greco, 2013), keratins and collagens are perhaps most studied (Toivola et al, 2015) and associated with various hair texture characteristics in several mammalian species including humans (Shimomura et al, 2010), dogs (Cadieu et al, 2009), horses (Balmer et al, 2017; Morgenthaler et al, 2017) and alpacas (Fan et al, 2011). Here we considered as candidate genes for alpaca hair texture also genes related to apoptosis regulation and formation of the hair follicle, such as CTNNB1 , TNFSF12 , and DAB2IP .…”
Section: Discussionmentioning
confidence: 99%
“…Melanogenesis involves a complex molecular regulation [7]. In order to understand the molecular mechanisms of coat color formation, previous studies have reported the generation of ESTs from both sheep and alpaca skin through traditional Sanger sequencing [16,17]. A previous study examined differences in gene expression associated with black spots in fleece of Corriedale sheep using microarray technology [18].…”
Section: Discussionmentioning
confidence: 99%
“…Melanocytes in black hair follicles contain the greatest number of melanosomes (which are eumelanosomes), while the melanosomes in brown hair bulbs are smaller and those in blonde hair are very poorly melanised. The relationship of less melanin with lighter skin/hair phenotype has been reported in several species, including humans [32], alpaca [17], llama [33] and horse [34]. In both domestic sheep and Soay sheep, light coat color is known to be due to a decrease in the ratio of eumelanin to pheomelanin, relative to black coat color [35].…”
Section: Discussionmentioning
confidence: 99%
“…Among the known genes for coat colour, the function of genes in the category related to 'the component of melanosome and their precursor' and 'Eumelanin and pheomelanin' are melanin synthesis and the switch between eumelanin and pheomelanin in the skin or hair [134,135]. The association between less melanin with lighter phenotype was observed in humans [136], alpacas [137], llamas [138], and horses [139]. This demonstrates that the AP1 family of TFs, especially the JUN family, plays an important role in melanin synthesis and expression of melanogenesis-associated genes.…”
Section: Potentially Cooperative Tf Pairs Directing Colour Patterning In Zebrafishmentioning
confidence: 99%